(untitled) (Eurasian Journal of Humanities and Social Sciences, 2021)
The advent of the internet caused some observers to mourn the imminent death of personal written correspondence, but the reality couldn’t be further from the prediction. Communication with others through texts, social media, and email is increasingly important. With that, more messages mean more potential for misunderstandings. In this article, we talk about why communication skills in English are so important; we’ll also give you tips for meeting today’s communication demands, whether English is your first language or whether you are learning it as an additional language skill.